DRAWINGS AND NARRATIVE: THE SELFCARE IN LEARNING OF PHYSICAL EDUCATION (Fiep Bulletin - online, 2017)
In addition to other curriculum subjects of basic education, physical education still uses traditional evaluationmethods. These instruments are limited and, compared to this, Michel Foucault presents clues to overcome this model. The aimof this article is to present the use of drawings and narratives as possible tools for evaluation of physical education learning. Themethodology used was of qualitative type, with the study field research as a technical procedure, narratives and drawings as datacollection instruments and two classes of students between 8 and 10 years old. The results obtained through drawings andnarratives show that students at the time of the narrative production and design, make a reflection of movement in the productionprocess, showing an occupation with himself, whatever Michel Foucault, and still represent the contents learned using alanguage that is their own. The final considerations are that the use of drawings and narratives as assessment tools are a goodoption for the teacher to measure the contents that were taught at the same time insert students in a reflection activity about you.